Emergency department visits and hospitalisations for emergent asthmatic symptoms from 2014 to 2016: cross-sectional study in Korea - Kyungseon Choi; Sola Han; Hae Sun Suh (BMJ Open)
Objective To evaluate the characteristics of emergent patients with asthma who visited emergency departments (EDs) in Korea, and the consequences of these visits.Design Retrospective cross-sectional study.Setting We used data from the National Emergency Department Information System database from 2014 to 2016. The data included reports collected from 408 EDs in Korea.Participants We analysed the ED cases for asthma-related emergent symptoms that met the following inclusion criteria: (1) had a main diagnosis code of asthma (International Classification of Diseases 10th Revision code: J45/J46), and (2) recorded as an emergent symptom in the EDs.Results During 2014–2016, there were 58 713 ED visits related to an asthma diagnosis with emergent symptoms. Following an ED visit, 31.69% were hospitalised, of which 89.88% were admitted to the general wards, and 10.12% to the intensive care units (ICUs). More than 50% of the hospitalised cases included in the group ≥70 years of age. The incidence of death during hospitalisation generally increased with age and the proportion of death in ICU exceeded 10% among the group ≥70 years. The ratio of ICU/general ward admission at the arrival time of 0–03:00, in the ≥60 years age group was the highest compared with other times of the day and age groups.Conclusions We found that among all age groups, ED visits by older patients resulted in more ICU admissions. Our results can help in providing a better understanding of medical resource utilisation by emergent patients with asthma.